Structure-to-Function Computational Prediction of a Subset of Ribosomal Proteins for the Small Ribosome Subunit - Ui-Hang, Edmund Sim; Chin-Ming, Er (International Academy Publishing (IAP), 2015)
Extra-ribosomal functions of ribosomal proteins have been widely accepted albeit an incomplete understanding of these roles. Standard experimental studies have limited usefulness in defining the complete biological significance of ribosomal proteins. An alternative strategy is via in silico analysis. Here, we sought a sequence-to-structure-to-function approach to computationally predict the extra-ribosomal functions of a subset of ribosomal proteins of the small ribosome subunit, namely RPS12, RPS19, RPS20 and RPS24. Three-dimensional structure constructed from amino acid sequence was precisely matched with structural neighbours to extrapolate possible functions. Our analysis reveals new logical roles for these ribosomal proteins, of which represent important information for planning experimental and further in silico studies to elucidate their physiological roles.